Digital Age Learning Among Malaysian School Administrators on Management and Instructional Technology: NETS-A - Ramalingam, Shanti; Saforrudin, Norabeerah binti; Mohd Yusof, Aziyah Binti; Salamat, Zubaidah Binti; Mohd Yusop, Noor Ashikin Binti; Zulkifeli, Mohd Afendi Bin; Ahmad, Mohd Yusof Bin (Advances in Social Sciences Research Journal, 2022)
The use of information and communication technology is a frequent approach applied in various organizations to ensure tasks are performed more smoothly. Administrators inspire and lead development and implementation of a shared vision for comprehensive integration of technology to promote excellence and support transformation throughout the organization. In examining this phenomenon, principals are expected to have trouble organizing technology in management and instructional based in school planning. This is because the use of technology is a formative nature technical and requires certain skills so that it can be integrated perfectly. This study was conducted to examine the level of competence of school administrators consisting of principals and head teachers on the management of instructional technology especially digital age learning and validate the elements in NETS-A. In addition, the study also aims to identify the level of technological leadership among principals in day primary schools based on the five dimensions of NETS-A namely visionary leadership, digital age learning culture, professional practice excellence, systemic improvement, and digital citizenship. This study uses survey techniques to obtain quantitative data. The respondents of this study consisted of 50 secondary schools from five states namely Pahang, Perak, Selangor, Terengganu and Negeri Sembilan. The findings of the study show that the level of competence of principals and head teachers in technology management is at a moderate level. Therefore, school administrators need to give their full commitment to the use of instructional technology in order to increase productivity in teaching and learning as well as school management.